Understanding Older Adults' Memory Distortion in the Light of Stereotype Threat - Mazerolle, Marie; Smith, Amy M.; Torrance, McKinzey; Thomas, Ayanna K. (Frontiers in Psychology, 2021)
Numerous studies have documented the detrimental impact of age-based stereotype threat (ABST) on older adults’ cognitive performance and especially on veridical memory (Lamont et al., 2015). However, far fewer studies have investigated the impact of ABST on older adults’ memory distortions. Here, we review the subset of research examining memory distortion and provide evidence for the role of stereotype threat as a powerful socio-emotional factor that impacts age-related susceptibility to memory distortion. In this review we define memory distortion as errors in memory that are associated with gist-based errors (e.g., Koutstaal & Schacter, 1997) or source misattributions (e.g., Mitchell et al., 2003).Whereas some of the reviewed experiments support the conclusion that ABST should be considered in the context of age-related differences in memory distortion, others reported little or no impact of stereotype threat. These discrepancies suggest that the role of ABST, and socio-emotional processes generally, in age-related changes in memory distortion are less clear. In this review, we argue that ABST does play an important role in age-related changes in memory distortion. We present evidence suggesting that discrepancies in the reviewed literature may be reconciled when evaluated in the context of the leading theories about stereotype threat: the Executive Resource Depletion hypothesis (ERD, Schmader et al., 2008) and the Regulatory Focus theory (RF, Barber, 2017). We also discuss how differences in methodology and participant characteristics can account for a priori contradictory results in the literature. Finally, we propose some recommendations for researchers and practitioners when assessing memory in older adults.